Iben Nagel Rasmussen: transparency in the maturity - Priscila de Queiroz Duarte (Revista Brasileira de Estudos da Presença, 2019)
Transparency is proposed as a quality that emerges from the career of the actress Iben Nagel Rasmussen, a representative of a laboratory dimension, of work on oneself in the European theater. An analogy is suggested between Han’s aromatic time and the quality of transparency. The artistic maturity of Stanislavski is a starting point to inquire about the meaning of the mature actor’s experiences, in light of the principles of the nô actor by Zeami. The quality of transparency in Rasmussen’s autonomy in relation to the Odin Teatret, in the creation of biographical performances, as well as pedagogical projects, and as a value to be cultivated in the contemporary scene is highlighted.